Labor Force and Unemployment in the 1920's and 1930's: A Reply - Coen, Robert M. (The Review of Economics and Statistics, 1973)
had a truly sensitive labor force series for the period before 1940. Indeed, to derive my aggregate employment series I estimated several hundred detailed employment series in order to reflect as best I could the true variability in that series, and thereby much of that in the unemployment series. And, though I made many checks to special censuses and city surveys, which did not disconfirm the unemployment figures, I emphasized the interpolations involved in the labor force series.6 We must recognize our ignorance, and the limitations of any data to portray those decades as lucidly as the powerful surveys of today permit. There is a clear alternative available to any model-maker who wants a different cyclical measure than that permitted by my labor force estimates. It is not to create a set of elasticities, assume them as constant, and infer that they permit us to test trend labor force participation rates. Nor is it to rely, half inadvertently, on series that appear more attractive because their derivation is less explicit. It is instead to include in the model specific additional measures. One obvious alternative is the standard Kuznet's income series (it being linked to different employment estimates than mine). The NBER cyclical indicators are another. Such cyclical measures can then be directly tested for their contribution to explain models of economic change during earlier decades, rather than through the screen of their contribution to shaping the measures against which we test models. 'Nor do I make the obvious point that linear interpolation between benchmark participation rates differential by age and sex permits interactions in the dynamic changes to net out. The result, however, would be inferior to that yielded by a perfectly specified model using superb and relevant data. (I omit reference to the various checks to benchmark figures made in my estimates for immigration, the impact of World War I on female participation rates etc.)